2019
DOI: 10.21608/ejnf.2019.79445
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Partial Replacement of Alfalfa Hay With Prickly Pear Peels ( Ppps) on Productive Performance of Rabbits.

Abstract: orty New Zealand white rabbits (NZW) male rabbits weighed 500+6 g were used in the present study to determine the effect of using residues prickly pear peels of a source of dietary feedstuffs on productive performance, digestibility, some blood constituents and Economic efficiency of rabbit. The animals were divided into four experimental groups of 10 rabbits each. The experimental diets replacing hay with prickly pear peels (ppps) at portion ( 0.0, ,25, 50 and 75%)) respectively. Results obtained could be sum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
1
2
0
Order By: Relevance
“…IVDMD values in cactus pear cladodes ranging from 48.5 to 86.6% were similarly recorded by several authors) [19,22,39,[59][60][61][62]. The high digestibility of all nutrients in treated groups [63] can be taken from the point that cacti contain minerals, which may be associated with improvement in the digestibility of all nutrients [26,36,64]. The IVDMD content in O. robusta was among the least performing O. ficus indica cultivars, while O. stricta var.…”
Section: In Vitro-dry Matter Digestibility (Ivdmd)supporting
confidence: 56%
See 1 more Smart Citation
“…IVDMD values in cactus pear cladodes ranging from 48.5 to 86.6% were similarly recorded by several authors) [19,22,39,[59][60][61][62]. The high digestibility of all nutrients in treated groups [63] can be taken from the point that cacti contain minerals, which may be associated with improvement in the digestibility of all nutrients [26,36,64]. The IVDMD content in O. robusta was among the least performing O. ficus indica cultivars, while O. stricta var.…”
Section: In Vitro-dry Matter Digestibility (Ivdmd)supporting
confidence: 56%
“…In Vitro Organic Matter Digestibility (IVOMD) Digestible organic matter is important for ruminal microbial protein synthesis as an energy source [55,63]. In the current study, the values of IVOMD showed a highly significant (p < 0.001) variation among the species and among cultivars.…”
Section: In Vitro-dry Matter Digestibility (Ivdmd)mentioning
confidence: 57%
“…In the current result, the high variability in the nutrient content of browse species could be associated with the inherent nature of the species. Digestible organic matter is important for ruminal microbial protein synthesis as an energy source (Costa et al, 2013;Bakr, 2019). Most of the browses and vegetable by products used in our study were low in fiber.…”
Section: Chemical Composition Of Common Browse Speciesmentioning
confidence: 85%